2015
DOI: 10.1002/dev.21308
|View full text |Cite
|
Sign up to set email alerts
|

Linking extremely low birth weight and internalizing behaviors in adult survivors: Influences of neuroendocrine dysregulation

Abstract: Young adult survivors of extremely low birth weight (ELBW; <1000 g) are known to be at elevated risk for internalizing problems, though little is known about the mechanisms that may lead to higher levels of psychopathology in this vulnerable group. We examined the moderating influence of neuroendocrine functioning on the link between being born at ELBW and internalizing behaviors at age 30-35. Salivary cortisol was collected 20 min after completion of a social stress task in 83 ELBW adult survivors and 89 norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Bagner et al found a correlation between cortisol reactivity and internalised behaviour and attention problems in premature children 18‐60 months old. Waxman et al studied neuroendocrine regulation by salivary cortisol measurements and internalising problems in surviving ELBW individuals born 1977‐1982 in Canada at 30‐35 years of age and found that higher afternoon values were correlated with internalising‐related behaviours. The authors suggested that different patterns of regulation of the neuroendocrine system in ELBW individuals might affect the development of psychopathology and contributed to the higher levels of anxiety and depressive symptoms seen in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Bagner et al found a correlation between cortisol reactivity and internalised behaviour and attention problems in premature children 18‐60 months old. Waxman et al studied neuroendocrine regulation by salivary cortisol measurements and internalising problems in surviving ELBW individuals born 1977‐1982 in Canada at 30‐35 years of age and found that higher afternoon values were correlated with internalising‐related behaviours. The authors suggested that different patterns of regulation of the neuroendocrine system in ELBW individuals might affect the development of psychopathology and contributed to the higher levels of anxiety and depressive symptoms seen in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…The stressful events during fetal and early postnatal development that result in preterm birth may influence brain development 40 and later stress responsiveness, possibly through changes in the hypothalamicpituitary-adrenal (HPA) axis. 41 Indeed, prenatal adversity may predispose individuals to becoming victims. 42 As peer victimization can lead to HPA dysregulation, 43,44 this may place children and adolescents born at ELBW at a greater disadvantage when they need to manage psychosocial stressors during development.…”
Section: Discussionmentioning
confidence: 99%
“…Due to advances occurring in fetal and neonatal medicine over the past several decades, the first generation of ELBW survivors have survived to adulthood and become parents. Even though preterm survivors appear to be more sensitive to stress and its effects 1,2 no studies have investigated the transmission of this stress vulnerability to their offspring. It is therefore important that we understand the impact of exposure to significant perinatal adversities both for survivors and for their offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Adverse early experiences can influence parenting and the transmission of personality phenotypes known to portend psychiatric risk of offspring. Indeed, previous research has shown that survivors of prematurity, particularly those born at extremely low birth weight (ELBW) have higher rates of shyness 1,2 , a stress vulnerability factor for mental illness and other adverse health, interpersonal, and vocational outcomes across the life span 3,4 . Until now, however, no one has had the opportunity to examine parenting among ELBW survivors and the transmission of their shy personality phenotype to their children.…”
Section: Introductionmentioning
confidence: 99%